The Synthesis Of Cuprous Oxide Nanowires In The Presence Of Oxygen Using A Hot Tube Thermal Evaporation Method - Muhammad Arif Khan; Samsudi Sakrani; Yussof Wahab; Rosnita Muhammad; Syahida Suhaimi (Penerbit UTM Press, 2024)
Vol 11, No 4